2016
DOI: 10.1371/journal.pntd.0005110
|View full text |Cite
|
Sign up to set email alerts
|

Migrant Workers in Malaysia: Current Implications of Sociodemographic and Environmental Characteristics in the Transmission of Intestinal Parasitic Infections

Abstract: A cross-sectional study of intestinal parasitic infections amongst migrant workers in Malaysia was conducted. A total of 388 workers were recruited from five sectors including manufacturing, construction, plantation, domestic and food services. The majority were recruited from Indonesia (n = 167, 43.3%), followed by Nepal (n = 81, 20.9%), Bangladesh (n = 70, 18%), India (n = 47, 12.1%) and Myanmar (n = 23, 5.9.2%). A total of four nematode species (Ascaris lumbricoides, Trichuris trichiura, Enterobius vermicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 24 publications
1
27
0
1
Order By: Relevance
“…6 Occasionally, sporadic cases occur in non-endemic, developed areas, because of immigration. 2 Therefore, to date, coming across a patient with parasite infection of T. trichiura in South Korea is highly rare in South Korea. However, North…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Occasionally, sporadic cases occur in non-endemic, developed areas, because of immigration. 2 Therefore, to date, coming across a patient with parasite infection of T. trichiura in South Korea is highly rare in South Korea. However, North…”
Section: Discussionmentioning
confidence: 99%
“…1 However, a few sporadic infections have been reported in non-endemic, developed countries, mainly in cases of immigrants. 2 Commonly, T. trichiura infection does not cause specific symptoms, except only patients with heavy infection. Severe colonic infection causes mucoid diarrhea, rectal prolapsed, and iron deficiency anemia, often resulting in growth retardation.…”
Section: Introductionmentioning
confidence: 99%
“…Further zoonotic studies were also undertaken in feral hosts in the Middle East and Far East, where Toxocara cati was dominant in feral cat populations from Qatar (Abu-Madi et al, 2010) and Peninsular Malaysia (Mohd Zain et al, 2013). Research on the epidemiology of zoonotic infections continues to thrive, with funding from the University of Malaya and the Ministry of Health, Kuala Lumpur on implications of socio-demographic determinants and environmental characteristics on the transmission of parasitic infections, including Toxocara and Toxoplasma, in migrant workers of Peninsular Malaysia (Sahimin et al, 2016(Sahimin et al, , 2017.…”
Section: Rollinsonmentioning
confidence: 99%
“…Enteric infectious diseases continue to be a major public health problem especially in low-and middleincome populations (1,2). Intestinal parasitic infections are one of the major causes of morbidity and mortality particularly in developing countries (3) and prevalence is known to be closely related to the educational levels of subjects, environmental factors, sanitary conditions, socio-economic status, inadequate medical care and lack of access to safe drinking water supplies (4)(5)(6). Studies have also shown that social and economic contexts are important determinants of human health, including diseases caused by parasitic organisms (2).…”
Section: Introductionmentioning
confidence: 99%